Accused: A Rosato & Associates Novel - Scottoline, Lisa; LaVoy, January; Wilson, Laura; Macmillan Audio (Firm) (New York : Macmillan Audio, 2013)
It begins with an astonishing request from a thirteen-year-old prospective client. Allegra Gardner's sister Fiona was murdered six years ago. It seemed like an open-and-shut case: the accused, Lonnie Stall, was seen fleeing the scene; his blood was on Fiona and her blood was on him; most damningly, Lonnie Stall pleaded guilty.
Keywords: Rosato & Associates (Imaginary organization) -- Fiction; Women lawyers -- Fiction; Murder -- Fiction -- Investigation; False imprisonment -- Fiction; Suspense fiction; Legal stories; Audiobooks